Advancements in the synergy of isothermal amplification and CRISPR-cas technologies for pathogen detection - Mao, Xiaolei; Xu, Minghui; Luo, Shuyin; Yang, Yi; Zhong, Jiaye; Zhou, Jiawei; Fan, Huayan; Li, Xiaoping; Chen, Zhi (Frontiers in Bioengineering and Biotechnology, 2023)
In the realm of pathogen detection, isothermal amplification technology has emerged as a swift, precise, and sensitive alternative to conventional PCR. This paper explores the fundamental principles of recombinase polymerase amplification (RPA) and recombinase-aid amplification (RAA) and reviews the current status of integrating the CRISPR-Cas system with RPA/RAA techniques. Furthermore, this paper explores the confluence of isothermal amplification and CRISPR-Cas technology, providing a comprehensive review and enhancements of existing combined methodologies such as SHERLOCK and DETECTR. We investigate the practical applications of RPA/RAA in conjunction with CRISPR-Cas for pathogen detection, highlighting how this integrated approach significantly advances both research and clinical implementation in the field. This paper aims to provide readers with a concise understanding of the fusion of RPA/RAA and CRISPR-Cas technology, offering insights into their clinical utility, ongoing enhancements, and the promising prospects of this integrated approach in pathogen detection.